United Arab Emirates : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper outlines a consolidated Medium-Term Fiscal Framework (MTFF), which is comprehensive and forward looking, could set a clear direction for fiscal policy for the country as a whole and better align resource allocation with local and national developments plans underpinned by goals embodied in the Vision 2021. High quality of public financial management systems overall is also key ingredient of an appropriate MTFF. The framework could consider explicitly expenditure needs in critical areas such as education and health care. Monitoring of contingent liabilities needs to be strengthened, including covering private and public partnerships (PPPs) and government related enterprises (GREs) including their global subsidiaries. Data sharing across all levels of governments, including the central bank, could also be strengthened. The federal government and the Emirates of Abu Dhabi and Dubai have started using MTFFs to inform their fiscal policy choices, albeit to different degrees.